Posredniška vloga slovarskih del 16. stoletja pri ohranjanju besedne zapuščine čakavca Jurija Juričiča v slovenskem knjižnem jeziku - Jelovšek, Alenka (Slovenski jezik, 2025)
This paper discusses the mediating role of the Register in Dalmatin’s Bible and Megiser’s multilingual dictionaries in the continuity of the words that were first attested in Juričič’s Postilla (1578) in the Slovenian literary language. An examination of the material in older Slovenian dictionaries shows that the Register in Dalmatin’s Bible did not play a special role either in the inclusion of Juričič’s words in Megiser’s dictionaries or in their inclusion in dictionaries from later periods of linguistic history, whereas the words that also appear in Megiser’s dictionaries show greater continuity.
Keywords: 16.st.; 16th cent.; dictionaries; Juričič, Jurij; knjižni jezik; leksikalna kontinuiteta; lexical continuity; slovarji; Slovenian language; slovenščina; standard language